Overused Dexamethasone Induced Exogenous Cushing’s Syndrome, Diabetes Mellitus, and Pneumonia - Dananjaya, Putu Gede Indra; Dewi, Ni Made Putri Purnama (Greenation Publisher & Yayasan Global Research National, 2024)
Cushing's syndrome is a collection of clinical symptoms resulting from excessive exposure to glucocorticoid hormones. The cause of Cushing's syndrome can be endogenous or exogenous factors. Exogenous factors caused by long-term use of corticosteroid drugs. Clinical manifestations that can be found include weight gain, often accompanied by a moon face, central obesity, fat deposits in the dorsocervical and supraclavicular areas, proximal muscle weakness, fatigue, leg edema, easy bruising, thinning skin, and striae. We report the case of a patient with exogenous Cushing's syndrome, diabetes mellitus, and pneumonia induced by excessive dexamethasone consumption accompanied by melena. Treatment should be carried out comprehensively by paying attention to the underlying disease. Discontinuation of glucocorticoids is the main treatment and needs to be done gradually. In this case, a stress dose of glucocorticoid was not given because he was experiencing gastrointestinal bleeding.